The modern state and trends of development of milk market in Ukraine - Voliak, Lesia; Sergiychuk, Nadiia (Turystyka i Rozwój Regionalny, 2018)
The article deals with the current state of the enterprises of the dairy industry of Ukraine. Analyzed the main indicators of the industry, the dynamics of milk prices and the main types of dairy products for the latter time, prices, import, and export. The main factors influencing the activity of the dairy industry of Ukraine are investigated. The urgent measures necessary to increase the level of development of the dairy industry and the output have been proposed Ukrainian enterprises to the European market.